Long-term Management of Kawasaki Disease: Implications for the Adult Patient - Cedric Manlhiot; Elizabeth Niedra; Brian W. McCrindle (Pediatrics and Neonatology)
Coronary artery complications from Kawasaki disease (KD) range from no involvement to giant coronary artery aneurysms (CAA). Current long-term management protocols are calibrated to the degree of maximal and current coronary artery involvement reflecting the known likelihood of severe long-term cardiac complications. It has recently been suggested that all KD patients may be at potential risk of severe long-term cardiac complications. If this assertion was to be confirmed, current follow-up protocols would need to be extensively modified, with important implications both for the growing adult population with a previous history of KD and for the healthcare system. Based on the available evidence, patients with multiple large and/or giant CAA are at substantial risk of severe long-term cardiac complications and should have regular specialized follow-up. Patients with transient or no CAA have not been reported to be at risk of severe long-term cardiac complications. The influence of KD on the atherosclerotic process remains suboptimally defined, and should be the focus of future studies. Heightened cardiovascular risk factor surveillance and management is recommended regardless of coronary artery involvement. Based on the currently available evidence, existing long-term management protocols seem to be appropriately calibrated to the level of risk. Revised long-term management protocols should incorporate newer, noninvasive imaging methods and intensive management of atherosclerotic risk. There is insufficient evidence at this time to mandate long-term specialized follow-up and invasive testing for patients who have not had CAA.